Small Changes Produce Large Gains in Efficiency: A Case Study from Ross Memorial Hospital - David Lane, Carol Findlay, Lisa Hickey and Ann Wehrstein (Healthcare Quarterly, 2013)
Healthcare is now more challenged to provide excellent care, while also increasing efficiency with more limited resources. The recent introduction of Ontario's funding reform challenges hospitals to increase the efficiency of specific procedures by providing funding based on patient volumes. The cataract surgery program at Ross Memorial Hospital, in Lindsay, Ontario, is an example of how a program designed a few years ago with a focus on patient care and efficiency managed to become substantially more efficient by introducing a series of small changes.
Keywords: eye suite, cataract surgery efficiency, eye program